58 letnikov Slavistične revije (1948-2010) - Dukič, Davorin (Slavistična revija, 2011)
The article surveys 62 years of publication of Slavistična revija (1948-2010), which resulted in 58 volumes. The author lays out and interprets the (mostly) quantitative results of the investigation, but the study focuses on the composition of editorial boards, their decisions, characteristics, of the publishing process, as well as the formal characteristics of the scholarly articles from the fields of Slavic and particularly Slovene linguistisc and literary criticism.
Keywords: 1848-2010; literarna kritika; literary criticism; Slavic languages; Slavistična revija (serijska publikacija); slovanske književnosti; slovanski jeziki; Slovene; Slovene literature; slovenska književnost; slovenske revije; slovenščina; znanstvene revije